Pendidikan Pesantren Dalam Perspektif Pendidikan Nasional - Setiawan, Agus; Norman, Efrita (International Conference on Islamic Studies, 2020)
This research is conducted to analyse national education perception towards Islamic education. In the Constitution of Republic of Indonesia 1945 article 3 section 3, there was at least two purposes of national education, which are increasing faith, piety, and moral. Based on that points, either directly or indirectly this section is addressed to religious-based education institutions, which one of them is Islam boarding school. In Constitution of Republic of Indonesia number 18 2019 related to boarding school, in article 15 stated that " Islamic boarding school (pesantren) is functioned as part of the implementation of national education" which means that boarding school is one of the operators of national education. In the regulation of SisDikNas number 20 2003, however was explicitly mentioned in chapter 1 article 1 section 2 that national education is an education based on Pancasila (Indonesian's Ideology) and the Constitution of Republic of Indonesia (UUD 45) which is rooted in values of religion. From the juridical fact above, based on Constitution, Islamic boarding school (Pesantren) has crucial role in realising the goals of national education.